Sustainable poultry waste management system to organic compost/ Faten Nor Anis ... [et al.] - Omar, Nur Faezah; A.H, Faten Nor Anis; S, Noor Zuhairah; Farhan, Najihah; M.H, Nurin Afrina (Universiti Teknologi MARA, Perak, 2023)
Composting is currently the best strategy to dispose wastes and turn them into something more stable as well as richer with nutrients. It can be combined with food waste, green waste, and animal waste, where composting process will start the biological decomposition of the substances under aerobic or anaerobic conditions. High demand and interest in the poultry sector have increased the poultry waste and sludge. Those nutrientrich wastes have a high potential to be innovated into something useful. Four completely randomized design treatments which are T1 (20% Chicken Dung + 60% Banana Trunk + 20% Egg shell), T2 (20% Chicken Dung + 60% Banana Trunk + 20% Chicken Bone), T3 (20% Chicken Dung + 60% Banana Trunk + 20% Chicken Feather) and T4 (20% Chicken Dung + 60% Banana Trunk + 20% Chicken Blood) were laid in an experiment where the parameters including nutrient analysis which were P, K, Ca, and Mg. Other parameters are temperature, pH value, electrical conductivity, and organic matter content. The result exhibited that combining the chicken dung, banana trunk and chicken feathers can have the most significant (p<0.05) effects towards the most important nutrients compared to other combination of materials treatments. (196 words)